Development of Foundation Engineering E-Module in Building Engineering Education Study Program, State University of Jakarta - Handoyo, Santoso Sri; Septiandini, Erna; Wukir, Diah Ayu; Pemungkas, Brahmansyah Rajif (Universitas Negeri Padang, 2024)
In the period of the fourth industrial revolution, technology plays an essential role in learning. Educators are working to improve the quality of learning by producing creative and exciting technology-based teaching materials that raise students' interest and ease of learning. One instance of technology being utilized in education is e-modules. The aim of this research is to develop e-module teaching materials for foundation engineering courses. Research and development model from Thiagarajan or 4D is used in this research. The four stages that were employed in this research are define, design, develop, and disseminate. This research sample consists of media expert validators, material expert validators and user evaluations. Validation findings from material specialists received an average evaluation percentage of 86%, while validation results from media experts obtained an average assessment percentage of 81%. This demonstrates that the development of e-module-based teaching materials for foundation engineering very suitable for use. Meanwhile, user evaluations on the creating of e-module-based foundation engineering teaching materials were deemed extremely acceptable for usage (average 89.3%). Based on the results of limited trials conducted on Building Engineering Education Students, it shows that the learning results of students have increased by 16.6% through a mean score of 70 on the pretest and 82 on the posttest.